Pengaruh Film Animasi Nussa dan Rara dalam Membentuk Karakter Anak Usia Dini - Anggy Widia Ramadanti; Padilah (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
The development of character values ​​can be done through mass media, both print and electronic. Through electronic media such as internet, TV, radio and cartoon media. Within the scope of PAUD, animated video media can be used as a more effective and efficient classroom learning method to develop character values ​​in children. This study aims to determine the effect of the animated film Nussa and Rara in shaping the character of children aged 4-5 years in the bright cheerful early childhood education in Palembang. The method in this study uses the Pre-Experimental method with the type of One-Group Pretest-Posttest Design. The sample used in this study is the class Al children, totaling 10 children. Data collection techniques using observation at the time of treatment to determine the results given. The results of the calculation of the t-test with a level of a(0.05) and dk 10-1=9 and the result of t_count is 14.67. Thus, it can be concluded that t_count > t_table or 14.67 > 2.26 then reject Ho and accept Ha. It means that the hypothesis stating that the animated film Nussa and Rara in shaping the character of children aged 4-5 years in Palembang's smart and cheerful early childhood is accepted as true.